Band Gap and Vibration Reduction Properties of Damped Rail with Two-Dimensional Honeycomb Phononic Crystals - Rixin Cui; Jinsong Zhou; Dao Gong (Shock and Vibration)
The prevention of environmental vibration pollution induced by train operation is one of the inevitable problems in the construction of urban rail transit. With the advantage of flexible adjustment, phononic crystals (PCs) have a broad application prospect in suppressing elastic wave propagation of rail transit. In this paper, a damped rail with two-dimensional honeycomb PCs was proposed, and its band structure was analysed with FEM. Then, a parametric study was used to investigate the influences of design parameters of the honeycomb PCs on its band gap property. Furthermore, with a 3D half-track model, the vibration reduction property of the damped rail with honeycomb PCs was discussed. The results show that the damped rail with honeycomb PCs has an absolute band gap in the frequency range of 877.3–1501.7 Hz, which includes the pinned-pinned resonance frequency of the rail internally. Reducing the filling fraction and elastic modulus of the matrix can obtain an absolute band gap in a lower frequency range but also bring a narrower bandwidth. The decrease of scatterer density leads to higher boundary frequencies of the absolute band gap and descends the bandwidth. In order to obtain an absolute band gap which can suppress the pinned-pinned resonance of the rail and keep a wider bandwidth, the filling fraction is suitable to be about 0.5, and the elastic modulus of the matrix is proposed to be not more than 0.6 MPa. Metals with heavy density can be used as the scatterer to obtain a better vibration reduction effect. It is hoped that the research results can provide a reference for the application of PCs in track vibration reduction.